ROLE OF ECOTOURISM IN SUSTAINABLE DEVELOPMENT: AN OVERVIEW (Journal of Pharmaceutical Negative Results, 2023)
A recent development in tourism is ecotourism. It is one of the tourism industry's fastest-growing subsectors. Ecotourism refers to any type of tourism that is focused on nature, has a little impact on the environment, includes locals in its planning and execution, and emphasises the importance of educating visitors. Ecotourism is distinct from other types of tourism because it is reliant on the maintenance of natural ecosystems so that they, and the cultural values they represent, can be experienced and appreciated by visitors. Many nations have come to rely on ecotourism as a major source of revenue. Ecotourism's ability to foster both economic growth and environmental protection in poor nations is exciting. This article will highlight the vast potential of Ecotourism in India by examining a few of the country's most popular Eco-tourism destinations. The present study also explores the emergence of ecotourism as an economic reader and the use of ecotourism as a tool for balancing environmental issues and sustainable development. This paper also includes a discussion of the government's efforts to promote ecotourism as a means of addressing modern environmental problems, as well as the results of a few studies of India's most popular ecotourism destinations.